Dealing with Paratextual Elements in Dubbing: A Pioneering Perspective from Catalonia - Matamala, Anna (Meta, 2011)
This article focuses on paratextuality in the realm of dubbing drawing on the author’s professional experience as an audiovisual translator in Catalonia. After a brief discussion of the theoretical approach to paratextuality and the notion of audiovisual text, the article lists the main paratextual components in dubbing and describes how they are dealt with by audiovisual translators. The article focuses on fiction films, cartoons and television series, be they for cinema, television, Internet or DVD, and considers paratexts at two levels: in the audiovisual text itself and in the written synchronised translation.